Feminism as a Class Act: Working-Class Feminism and the Women's Movement in Canada - Luxton, Meg (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2001)
Abstract There is a widespread claim that the women's movement of the 1960s and 1970s was middle-class and that its politics of reforming the state reflected the concerns of middle-class women. This paper challenges that claim, arguing instead that the development of the women's movement created an environment in which a union-based, working-class feminism became an important political factor. Working-class and socialist-feminist activists developed a strong feminist presence in the labour movement and a significant working-class orientation in the women's movement that both continue to influence the current women's movement.